2021
DOI: 10.1186/s13028-021-00582-2
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in Swedish show dogs–prevalence and association with performance in competition

Abstract: Background The prevalence of overweight and obesity is increasing in companion dogs, but little is known of these conditions in show dogs. This study assessed body condition score (BCS) of show dogs of six selected popular breeds at a major Swedish dog show event and examined the association between BCS and performance in competition. Results At one of Sweden’s largest dog shows, BCS of 120 dogs of six different breeds was assessed by trained anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
12
2
Order By: Relevance
“…Concerns for a general trend towards heavier show dogs, both older and younger, are being discussed 23 , 38 , even though recommended BW and height in breed standards have not changed for the last decades. In consistency with the internationally published figures, a recent study on Swedish show dogs found 32% of the dogs being overweight 23 . The observed decrease in mean BW in several breeds in our study might as previously mentioned, relate to either changes in size or body condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns for a general trend towards heavier show dogs, both older and younger, are being discussed 23 , 38 , even though recommended BW and height in breed standards have not changed for the last decades. In consistency with the internationally published figures, a recent study on Swedish show dogs found 32% of the dogs being overweight 23 . The observed decrease in mean BW in several breeds in our study might as previously mentioned, relate to either changes in size or body condition.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally reported prevalence of overweight and obesity in dogs is high, and seems to be increasing [18][19][20][21][22]24,38 . Concerns for a general trend towards heavier show dogs, both older and younger, are being discussed 23,38 , even though recommended BW and height in breed standards have not changed for the last decades. In consistency with the internationally published figures, a recent study on Swedish show dogs found 32% of the dogs being overweight 23 .…”
Section: Breedmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that diet and body condition have a combined effect in changing the gut microbiota in dogs [ 23 , 24 , 26 , 48 ] and studies of causality are therefore complicated. Our study is based on a common dog breed, that may often be slightly overweight [ 49 ]. Furthermore, the data are generated from dogs living in a regular home environment, not exposed to any dietary intervention or body weight manipulation during sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the incidence of this problem in dogs vary according to different authors. Studies in recent years have shown that the prevalence of canine obesity varies between 25 and 44% in developed countries [ 21 , 22 , 23 ]. The prevalence of obesity in dogs is increasing [ 24 ].…”
Section: Introductionmentioning
confidence: 99%